2021
DOI: 10.1002/poc.4204
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical design of near‐infrared sensitive fused ring electron acceptors containing selenophene as π‐bridge for high‐performance organic solar cells

Abstract: End-capped acceptors modification of fused ring electron acceptors (FREAs) is an attractive strategy to boost the optoelectronic and photovoltaic properties of the materials. FREAs are also proven beneficial due to their tremendous applications in organic solar cells (OSCs). Among fused-ring electronic species, small fullerene-free FREAs have already been drawn more attention due to their near-infrared sensitivity and constantly increasing efficiencies. Therefore, we have designed six new FREAs (K1-K6) having … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 70 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…Previously, we have reported the zinc‐phthalocyanines, 34 as better performing photovoltaic materials for OSCs construction. Also, some bridge modifications have been reported earlier and our results obtained are much better 35‐37 . In the present work, we have designed eight new molecules ( X1‐X8) shown in Figures 1 and S1 (optimized geometries in Data S1) and examined their photovoltaic performance on different parameters.…”
Section: Introductionmentioning
confidence: 53%
See 1 more Smart Citation
“…Previously, we have reported the zinc‐phthalocyanines, 34 as better performing photovoltaic materials for OSCs construction. Also, some bridge modifications have been reported earlier and our results obtained are much better 35‐37 . In the present work, we have designed eight new molecules ( X1‐X8) shown in Figures 1 and S1 (optimized geometries in Data S1) and examined their photovoltaic performance on different parameters.…”
Section: Introductionmentioning
confidence: 53%
“…Also, some bridge modifications have been reported earlier and our results obtained are much better. [35][36][37] In the present work, we have designed eight new molecules (X1-X8) shown in The results suggested that the newly designed molecules displayed better performance as photovoltaic material based on all the above-mentioned properties.…”
Section: Introductionmentioning
confidence: 81%
“…The HOMO–LUMO energy gap also determines the sensing ability and charge transfer within a system. The band gap (HOMO–LUMO energy gap) of a system can be calculated by utilizing the following equation. …”
Section: Resultsmentioning
confidence: 99%
“…The density of states (DOS) spectrum interpretation is a special criterion to estimate the working efficiency of a solar cell. , DOS shows the nature of all linking groups (that are present in a molecule) with charge-transfer behavior. DOS is a pure quantum mechanical technique which also estimates the presence of electron density per unit area in a molecule.…”
Section: Results and Discussionmentioning
confidence: 99%